Examining Demographic and Preadmission Factors Predictive of First Year and Overall Program Success in a Public Physical Therapist Education Program. Issue 3 (7th September 2021) - Mitchell, Katy; Ellison, Jennifer; Schaumberg, Elke; Gleeson, Peggy; Bickley, Christina; Naiki, Anna; Travis, Severin
Abstract : Introduction: Despite an increase in the rigor of entry-level Doctor of Physical Therapy (DPT) program admission, programs still struggle with student retention and success. The purpose of this study was to examine demographic and preadmission factors predictive of first year and overall program success in an entry-level public physical therapist education program. Subjects: Retrospective data from 473 DPT students at the Texas Woman's University in Houston, TX, who entered the program between 2010 and 2018. Methods: This study included the following predictor variables: last 60 hours undergraduate (UG) grade point average (GPA), UG math/science GPA, overall UG GPA, science/nonscience major, Graduate Record Examination (GRE) component scores, GRE summed score (GRE-S), size and type of UG institution (dichotomized), gender, age, and personal grit score. Success in the program was measured by first-semester GPA, cumulative third-semester GPA, final program GPA, three-tiered ranking of academic and clinical education (CE) standing, completion of first-year program, and completion of the entire 3-year program. Results: First-year program success (first-semester GPA, cumulative third-semester GPA, and first-year completion) was predicted by age, overall UG GPA, GRE-S, and all GRE components. GRE scores and UG GPA when entered together predicted 45.8% of the first-year GPA. Overall program success was predicted by UG GPA, GRE-S, and all GRE components. GRE-S and UG GPA when entered together predicted 34.8% of final program GPA. Academic standing was predicted by multiple predictors, whereas CE performance was only predicted by 2 components of the GRE and GRE-S. When comparing students who completed the program versus those who did not, significant differences were found in all GRE components and overall UG GPA. Receiver-operating-characteristics analysis was used to determine cutoff scores for the GRE and overall UG GPA, which best predict first-year and program retention. Conclusion: Admissions committees of DPT should analyze their program-specific data to better guide their admissions decisions. Overall UG GPA and GRE continue to be strong predictors of physical therapist program success. In order to increase retention rates, DPT programs should consider additional resources for students who may be at risk.